Land Use Change and Sustainability - Appiah-Opoku, Seth (IntechOpen, 2020)
This book discusses aspects of land use change and sustainability in ways that may generate further research ideas. It brings together discussions from leading researchers and scholars in the field of land use change and sustainability from five different countries including the USA, Ethiopia, Guyana, Taiwan, and Indonesia. Based on empirical research and case studies, the book is divided into two sections. The first section is subdivided into four chapters and discusses land use sustainability in the Northern Great Plains of the USA; effects of rural land use and tenure on sustainable management of mangroves in Corentyne, Guyana; the property formation process in peri-urban areas of Ethiopia; and the effects of green energy production on farmlands in the Yulin County of Taiwan. The second section of the book is subdivided into two chapters and discusses cases pertaining to land use mapping and sustainability including land cover/land use mapping using soft computing techniques with optimized features; and applying systems analysis to evaluate Jelutung as option for sustainable use of peat lands in Central Kalimantan, Indonesia. The book is insightful, thought provoking, concise, and easy to understand. It could serve as an important reference material on land use change and sustainability.